Effectiveness of Field Trip Learning Towards Batik Banten Curriculum in Elementary School - Minhatul Ma'arif; Rizal Fauzi (Universitas Muhammadiyah Mataram, 2018)
This research is backed by the low creativity of elementary school students in the subjects of arts culture and Skills (SBK). The material taken is related to the batik curriculum in Banten in accordance with the PERGUB BANTEN 2014 that requires the entire school to integrate the local content curriculum of batik Banten. This research aims to increase the creativity of students in the local content curriculum in SBK subjects. This research uses class action research (PTK) with the number of students from 100 Grade 5 students elementary school who come from 4 (four) elementary schools in Panimbang, Pandeglang District by joining field trip activities. The results of the study were obtained through 2 (two) cycles, each cycle consists of 2 (two) meetings with a time allocation of 2 x 30 minutes. Based on the analysis of the research results obtained that there is no increase between the filed trip with the increase of student creativity on the field trips in integrating the curriculum batik. At the instructor's activity only increased by 0.5%, while in student activity only increased by 13.5%. Although the percentages are increasing, they remain in the